Adsorption Of Selected Dyes By Chemically Modified Uncaria Gambir Extract - Achmad, Azraa (2012)
Uncaria gambir extract was chemically modified to develop a novel adsorbent for the adsorption of Methylene Blue (MB), Sunset Yellow FCF (SY), and Direct Red 23 (DR 23) from aqueous solution. It was revealed that the ethyl acetate extraction of gambir showed highest total phenolic and total flavonoid contents. The gambir extract was subjected to pretreatment with formaldehyde and hydrochloric acid to produce the modified gambir adsorbent (MGA) which was then characterized by Fourier transform infrared (FTIR) spectroscopy,